Characterization of porous bovine hydroxyapatite (BHA) structures and their porous composites with inert glass (CIG) - (:unkn) unknown (European Powder Metallurgy Association (EPMA), 2011)
Calcium phosphate, which is a major inorganic component of the natural bone, has been successfully used in orthopaedic and dental applications for more than 20 years. Hydroxyapatite (HA) materials feature great biocompatibility with the human body, but their poor mechanical properties limit their applications for load-bearing devices. Porous scaffolds of HA, derived from calcined bovine bones and doped with reinforcing material commercial inert glass (CIG), were produced with adding 20wt% carbamide with respect to the batch, and sintering between 1100-1300°C. Porosity, density and SEM studies were investigated. The use of carbamide, as proposed in the present study, is an economic and simple way of producing porous HA scaffolds with no risk of leaving harmful residues (like naphthalene) in the final porous scaffolds after firing and sintering. The aim of this study was to develop porous highly bioactive scaffold structures of composites of HA doped CIG.
Keywords: Commercial inert glass; Composites; Hydroxyapatite; Porous